Preclinical Studies of a Novel Human PD-1 B-Cell Peptide Cancer Vaccine PD1-Vaxx From BALB/c Mice to Beagle Dogs and to Non-Human Primates (Cynomolgus Monkeys) - Guo, Linlin; Overholser, Jay; Good, Anthony J.; Ede, Nicholas J.; Kaumaya, Pravin T. P. (Frontiers in Oncology, 2022)
Immunotherapy with monoclonal antibodies to checkpoint inhibitors against the PD-1/PD-L1 signaling pathway is a landmark achievement in cancer therapy. Some anti-PD-1 inhibitors such as nivolumab and pembrolizumab have shown clinical success, in a percentage of patients with prolonged survival rates. However, adverse effects accompany these benefits. In this case, strategies with lower toxicity and increased specificity are urgently required. Cancer vaccines have the ability to stimulate the native immune system and in particular, an engineered B-cell epitope can elicit high-affinity polyclonal antibodies with similar efficacy to PD-1 monoclonal antibodies in murine animal models. We have previously designed and synthesized a unique B-cell vaccine, PD1-Vaxx [MVF-PD-1(92-110)], and we have tested the immunogenicity and antitumor properties in CT26 colon cancer BALB/c syngeneic mice model. This manuscript provides results from comprehensive preclinical pharmacology studies encompassing primary and secondary pharmacodynamics, biodistribution, and safety studies. The results from these preclinical studies support the use of PD1-Vaxx in a first-in-human clinical trial in patients with non-small cell lung cancer (NSCLC). A phase I trial in patients with NSCLC has commenced.